Have we been wrong? Generation Z’s tourism students’ complex relationship with work-related preferences - Engström, Truls Eric Johan; Gorenak, Mitja; Špindler, Tomi; Jagodič, Gregor (Turyzm/Tourism, 2025)
The article investigates the work preferences of Generation Z tourism students, emphasising their distinct expectations towards work-related preferences. Generation Z, born between 1995 and 2012, has now extensively entered the labour market and is currently marked as a generation with a strong demand for flexibility, digitalisation and teamwork. A survey involving 142 Generation Z tourism students from three European faculties explored their preferences regarding working time flexibility, remote work and value orientation. The findings reveal that Generation Z tourism students prefer a combination of fixed and flexible working hours and favour on-site over remote work. Interestingly, despite being open to dynamic challenges, they enjoy routine tasks specific to the tourism industry and, moreover, they are highly teamwork-oriented and seek meaningful work beyond just financial goals. This article provides valuable insights into the needs of Generation Z tourism students and highlights the gap between employers’ expectations and the actual desires of these future workers regarding employment in tourism. Adapting job roles to align with these preferences could significantly attract more members of Generation Z to the tourism sector.